2015
DOI: 10.1172/jci78488
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of microRNA-150 silencing disadvantages crizotinib-resistant NPM-ALK(+) cell growth

Abstract: International audienceno abstrac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 79 publications
0
38
0
Order By: Relevance
“…Though the interplay between those microRNAs in autoimmunity progression is not fully comprehended, lessons can be learned by myasthenia gravis (MG), an autoantibody-mediated neuromuscular disorder (Punga et al 2015). MicroRNA-21 via inhibition of RASGRP1 gene expression downregulates DNA methyltransferase1 (DNMT1), and methylation-silencing of miR-150 gene by DNMT1 as recently reported (Hoareau-Aveilla et al 2015). Thus, we speculate that miR-21 may indirectly modulate miR-150 expression by downregulation of RASGRP1 that reduces expression of DNMT1 and hypomethylation may lead to the upregulation of miR-150 gene.…”
Section: Discussionmentioning
confidence: 98%
“…Though the interplay between those microRNAs in autoimmunity progression is not fully comprehended, lessons can be learned by myasthenia gravis (MG), an autoantibody-mediated neuromuscular disorder (Punga et al 2015). MicroRNA-21 via inhibition of RASGRP1 gene expression downregulates DNA methyltransferase1 (DNMT1), and methylation-silencing of miR-150 gene by DNMT1 as recently reported (Hoareau-Aveilla et al 2015). Thus, we speculate that miR-21 may indirectly modulate miR-150 expression by downregulation of RASGRP1 that reduces expression of DNMT1 and hypomethylation may lead to the upregulation of miR-150 gene.…”
Section: Discussionmentioning
confidence: 98%
“…KLF2 is involved in lymphocyte biology (55), and miR-150 is involved in T-cell lineage commitment (56), B-cell differentiation (57), and natural killer cell development (58,59). In independent work, low miR-150 expression has been reported frequently for mantle cell lymphoma and in natural killer cell and T-cell lymphomas; furthermore, a loss of miR-150 contributes to increased proliferation, decreased apoptosis, and drug resistance in these malignancies (26,(60)(61)(62). Our work supports a role for both KLF2 and KLF4 regulation of miR-150 in hematopoietic malignancies but suggests that the loss of KLF4 is the major regulator in AML.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recurrent activating mutations of JAK1 and/or STAT3 genes have been identified in 20% of cases (Crescenzo et al , ) and MIR155 overexpression has been detected (Merkel et al , , ). Undoubtedly as techniques develop, more defining (epi)genetic events will be described and other studies for example, have identified alterations to the epigenome in ALCL inclusive of CpG methylation and expression or down‐regulation of small non‐coding RNA sequences including miRNAs (Ambrogio et al , ; Merkel et al , , ; Zhang et al , ; Hoareau‐Aveilla et al , ).…”
Section: Genetics and Molecular Findingsmentioning
confidence: 99%